Prevention, screening and treatment of colorectal cancer: a global and regional generalized cost effectiveness analysis - Johns Benjamin P; Lauer Jeremy A; Lim Stephen S; Ginsberg Gary M; Sepulveda Cecilia R (Cost Effectiveness and Resource Allocation, 2010)
Abstract Background Regional generalized cost-effectiveness estimates of prevention, screening and treatment interventions for colorectal cancer are presented. Methods Standardised WHO-CHOICE methodology was used. A colorectal cancer model was employed to provide estimates of screening and treatment effectiveness. Intervention effectiveness was determined via a population state-transition model (PopMod) that simulates the evolution of a sub-regional population accounting for births, deaths and disease epidemiology. Economic costs of procedures and treatment were estimated, including programme overhead and training costs. Results In regions characterised by high income, low mortality and high existing treatment coverage, the addition of screening to the current high treatment levels is very cost-effective, although no particular intervention stands out in cost-effectiveness terms relative to the others. In regions characterised by low income, low mortality with existing treatment coverage around 50%, expanding treatment with or without screening is cost-effective or very cost-effective. Abandoning treatment in favour of screening (no treatment scenario) would not be cost effective. In regions characterised by low income, high mortality and low treatment levels, the most cost-effective intervention is expanding treatment. Conclusions From a cost-effectiveness standpoint, screening programmes should be expanded in developed regions and treatment programmes should be established for colorectal cancer in regions with low treatment coverage.